2018
DOI: 10.1186/s12933-018-0709-9
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic effects of saxagliptin and metformin on CD34+ endothelial progenitor cells in early type 2 diabetes patients: a randomized clinical trial

Abstract: AimsType 2 diabetes is associated with endothelial dysfunction leading to cardiovascular disease. CD34+ endothelial Progenitor Cells (EPCs) are responsible for endothelial repair and neo-angiogenesis and can be used as a cardiovascular disease risk biomarker. This study investigated whether the addition of saxagliptin, a DPP-IV inhibitor, to metformin, may reduce cardiovascular disease risk in addition to improving glycemic control in Type 2 diabetes patients.MethodsIn 12 week, double-blind, randomized placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 58 publications
3
34
0
1
Order By: Relevance
“…In support of this we also found significant increase in the endothelial markers and functional genes (PECAM1, VEGF-A and vWF and NOS3) in linagliptin group as compared to placebo group (Figure 2A ). These observations are in agreement with our previous published results suggesting patho-physiological role of ROS activation and therapeutic reduction in CD34+ve cells in diabetes (33).…”
Section: Primary Outcome: Cellularsupporting
confidence: 94%
“…In support of this we also found significant increase in the endothelial markers and functional genes (PECAM1, VEGF-A and vWF and NOS3) in linagliptin group as compared to placebo group (Figure 2A ). These observations are in agreement with our previous published results suggesting patho-physiological role of ROS activation and therapeutic reduction in CD34+ve cells in diabetes (33).…”
Section: Primary Outcome: Cellularsupporting
confidence: 94%
“…Metformin activates AMPK phosphorylation, which reduces oxidative stress, reduces the production of inflammatory cytokines, and increases eNOS (endothelial nitric oxide synthase) activity, which may be an important mechanism for metformin cardiovascular protection. Recent studies have also shown that metformin has protective effects on vascular endothelial function and angiogenesis [72], which may be the pathway of metformin's cardiovascular protective effects. However, this protective effect also has some limitations.…”
Section: Discussionmentioning
confidence: 98%
“…With the highest expression specificity in vascular endothelial cells, CD34 has been termed a pan-endothelial cell marker and is superior to other markers of endothelial cells. 22 Therefore, CD34 + endothelial cells were used for detection in miR145 mimic/ inhibitor-transfected RAECs to verify the proliferation of specific endothelial cell populations. Detection turned out to verified successfully, because miR145 mimics boosted the expression of CD34 + endothelial cells in RAECs.…”
Section: Discussionmentioning
confidence: 99%